Private wells—building resilience to wildfires - Juliette O’Keeffe (Environmental Health Review, 2026)
About one in 10 households in Canada relies on a private well as their primary drinking water source, and as unregulated water supplies, the responsibility for managing drinking water safety lies with the well owner. Rural and remote communities with a higher reliance on private wells may be more exposed to climate-related hazards such as wildfires. Wildfires can damage well infrastructure, affect catchment hydrology, and potentially cause new pathways for biological or chemical contaminants to reach well water. After a wildfire, well owners may require additional support to assess damages and contamination, restore drinking water safety, and test their water quality, and this paper provides an overview of the evidence-based guidance that can support preparedness, response and recovery. Building resilience to wildfires includes uptake of well stewardship practices such as routine inspection, maintenance, and testing; however, longstanding barriers to well stewardship, particularly low risk perception, remain. Framing well stewardship as an essential part of emergency preparedness and climate resilience, could help improve engagement among well owners.